Out-Of-Wedlock Pregnancy In Early Adulthood: Meaning Of Life And Psychological Well-Being - Mentari, Ulva Widia; Sujadi, Eko (Educational Guidance and Counseling Development Journal, 2025)
Women experiencing out-of-wedlock pregnancies encountered challenges in determining the meaning of life and their psychological well-being. This study aimed to investigate the meaning of life and psychological well-being in women in this situation. The study employed a qualitative case study design. The researcher engaged three female informants experiencing pregnancies outside of marriage selected through purposive sampling. Semi-structured interviews were conducted to delve into the informants' perspectives. The two main themes that emerged were the meaning of life and psychological well-being. The research findings highlighted that the meaning of life was a crucial aspect for women experiencing out-of-wedlock pregnancies in their quest for self-identity. Similarly, psychological well-being was vital for them. Common psychological challenges included stigma, but strategies such as intensive communication with family and the community helped overcome these issues. The experience of being pregnant outside of marriage brought awareness of past mistakes and a motivation to improve relationships with family and society. This study emphasized the urgent need for the meaning of life and psychological well-being to assist women with out-of-wedlock pregnancies in improving their futures.